Cingulo-Opercular and Frontoparietal Network Control of Effort and Fatigue in Mild Traumatic Brain Injury - Ramage, Amy E.; Ray, Kimberly L.; Franz, Hannah M.; Tate, David F.; Lewis, Jeffrey D.; Robin, Donald A. (Frontiers in Human Neuroscience, 2022)
The neural substrates of fatigue in traumatic brain injury (TBI) are not well understood despite the considerable burden of fatigue on return to productivity. Fatigue is associated with diminishing performance under conditions of high cognitive demand, sense of effort, or need for motivation – all of which are associated with cognitive control brain network integrity. We hypothesize that the pathophysiology of TBI results in damage to diffuse cognitive control networks, disrupting coordination of moment-to-moment monitoring, prediction, and regulation of behavior. We investigate the cingulo-opercular (CO) and frontoparietal (FP) networks, which are engaged to sustain attention for task performance and to maintain performance. 61 individuals with mild TBI and 42 orthopedic control subjects participated in functional MRI during performance of a Constant Effort task requiring altering the amount of effort (25%, 50% or 75% of maximum effort) utilized to manually squeeze a pneumostatic bulb across six, 30-second trials. Network-based statistics assessed within-network organization and fluctuation with task manipulations by group. Results demonstrate small group differences in network organization, but considerable group differences in the evolution of task-related modulation of connectivity. The mild TBI group demonstrated elevated CO connectivity throughout the task with little variation for effort level or time on task, while CO connectivity diminished over time in the Controls. Several interregional CO connections were predictive of fatigue in the TBI group. In contrast, FP connectivity fluctuated with task manipulations and predicted fatigue in Controls, but connectivity fluctuations were delayed in the mTBI group and did not relate to fatigue. These group differences in the timing of peak connectivity suggest hyper-connectivity of the CO with increasing effort level and time on task, and/or hypo-connectivity and limited task-related modulation of the FP in TBI, neither being well-suited to attain task goals and results in fatigue. Findings are discussed in relation to performance monitoring of prediction error that relies on internal cues from sensorimotor feedback during task performance. The delay or inability to detect and respond to prediction errors in TBI, particularly evident in bilateral insula-temporal CO connectivity, corresponds to more day-to-day fatigue and fatigue during task performance.